Israel's election. Issue 3 (16th March 2019) - Unknown
Abstract : Israeli Prime Minister Benjamin Netanyahu appears most likely to form Israel's next government following its election on 9 April, although it is unclear how stable such a government would be. Further elections within the next two years are quite possible. Whatever the outcome of the election, Israel's next leader will be forced to address a range of serious and interrelated strategic challenges.